Students’ Mathematical Reasoning in Learning of Transformation Geometry - Rosa Amalia Adiafidah; Abd Qohar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Mathematical reasoning is component that must be built by students. Mathematical reasoning plays an important role in solving problems and delivering ideas in learning mathematics. Students learn that reasoning is not just how to convince themselves and friends but also to convince the wider community of a class. Furthermore, reasoning can be a vehicle for shaping mathematical knowledge that can be developed, and accessed by members of the community in the class. Geometry transformation material is one material that is very close to everyday life. This research is a qualitative descriptive study that aims to describe the mathematical reasoning of students in learning the transformation geometry. The subjects in this study were students of class XI MIPA 5 in MAN Batu, Malang, East Java. Through the process of mathematical reasoning, students are able to fulfill basic competencies, namely analyzing and comparing transformation and composition of transformations using matrix.